2019
DOI: 10.3389/fpsyg.2019.01033
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Allopregnanolone in Pregnancy in Predicting Postpartum Anxiety Symptoms

Abstract: Postpartum depression is a serious illness affecting up to 15% of women worldwide after childbirth, and our understanding of its biology is limited. Postpartum anxiety is perhaps more prevalent and less understood. Prior studies indicate that allopregnanolone, a metabolite of progesterone, may play a role in reproductive mood disorders, including postpartum depression, but the exact nature of that role is unclear. Our own prior study in a group of psychiatrically ill women found that low allopregnanolone in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…The increase in plasma progesterone throughout pregnancy triggers upregulation of allopregnanolone levels, which reaches the highest blood concentrations during the third trimester (49,50). Following childbirth, these neurohormones abruptly decrease (51,52). Among the hypotheses linking allopregnanolone decrease and post-partum depression, the suggestion that allopregnanolone drops quicker and to lower levels than in mothers who fail to develop post-partum depression is particularly intriguing.…”
Section: Mechanisms Linking Biosynthesis Of Allopregnanolone To Mood Disordersmentioning
confidence: 99%
“…The increase in plasma progesterone throughout pregnancy triggers upregulation of allopregnanolone levels, which reaches the highest blood concentrations during the third trimester (49,50). Following childbirth, these neurohormones abruptly decrease (51,52). Among the hypotheses linking allopregnanolone decrease and post-partum depression, the suggestion that allopregnanolone drops quicker and to lower levels than in mothers who fail to develop post-partum depression is particularly intriguing.…”
Section: Mechanisms Linking Biosynthesis Of Allopregnanolone To Mood Disordersmentioning
confidence: 99%
“…Osborne et al ( 111 ) found that TTC9B and HP1BP3 DNA methylation in early antenatal stage showed moderate association with the change in estradiol and ALLO levels over the course of pregnancy, suggesting that epigenetic variation at these loci may be important for mediating hormonal sensitivity, and that PPD is mediated by differential gene expression and epigenetic sensitivity to pregnancy hormones and thus modeling proxies of this sensitivity may enable accurate prediction of PPD. Osborne et al ( 38 ) further found an association between lower ALLO levels in the second trimester of pregnancy and an elevated risk of developing PPD, which seem to have been confirmed by latest studies ( 39 , 49 , 112 114 ), and can be traced back to the two genes identified above. Indeed, this seems to have gathered more support than many other biomarkers.…”
Section: Biological Predictors and Biomarkers For Ppdmentioning
confidence: 73%
“…Previously, Bloch et al ( 121 ) found that women with a PPD history are more sensitive to mood-destabilizing effects of gonadal steroids than healthy controls. Rather than progesterone withdrawal upon delivery, it has been found that a low ALLO level during pregnancy predicts PPD ( 38 , 112 , 114 ). Such an association was also found in earlier studies ( 126 , 127 ).…”
Section: Biological Predictors and Biomarkers For Ppdmentioning
confidence: 99%
“…For instance, anxiety-like behavior and depression are associated with decreased plasma and/or CSF levels of THP (Frye et al, 2008a;Maguire, 2019;Romeo et al, 1998;Rupprecht and Holsboer, 1999;Rupprecht et al, 2010;Schule et al, 2014;Walf and Frye, 2012). Similar changes have been observed in women affected by post-partum depression (Osborne et al, 2017) or post-partum anxiety (Osborne et al, 2019). THP and 3α-diol plasma levels are also decreased in association with increased depression and anxiety symptoms in anorexic and overweight/obese women (Dichtel et al, 2018).…”
Section: Alterations In Steroidogenic Enzymes and Steroid Levelsmentioning
confidence: 86%